Echoes of the Past: Drowned Forests and Indigenous Cultural Connections in Inundated Coastal Landscape - Ingrid Ward; David R. Guilfoyle; Doc (Ronald) Reynolds (Heritage)
Subfossil trees in growth position and their associated organic sediments serve as valuable archives of past ecologies, shedding light on coastal forest responses to post-Glacial sea-level rise. This paper offers an overview of the significance of drowned forests as both ecological and cultural records, with particular emphasis on Australian Indigenous connections to these landscapes. Indigenous use of and cultural connections to coastal trees and forests in Australian contexts are outlined, along with an overview of the formation and preservation processes of submerged forests and the methodological approaches used to study them. Case studies from across Australia illustrate the diversity of these records and their relevance to both science and heritage. The paper highlights the need for a regional database of subfossil trees and peats and underscores the importance of integrating Indigenous and scientific knowledge systems to deepen our understanding of environmental and cultural change.